Pengaruh Kreativitas dan Kecerdasan Musikal Terhadap Fungsi Eksekutif Anak TK B di Telaga Asih Jawa Barat - Naif, Maria Marlena; Susanti, Debie (Universitas Cokroaminoto Palopo, 2024)
This research aims to investigate the influence of creativity and musical intelligence on the executive function of Kindergarten B children in West Java province, especially in Kel. Telaga Asih. The survey method was used with a quantitative approach, regression analysis, F test, and SPSS. The questionnaire was filled out by parents from 4 kindergartens who were randomly selected using the multistage custom random sampling method. Data obtained from the parent questionnaire will be processed using the regression analysis method to investigate the relationship between creativity and musical intelligence and the executive function of Kindergarten B children. The F test will be used to test the significance of this relationship. It is hoped that the results of this research will provide a better understanding of the influence of creativity and musical intelligence on the executive function of Kindergarten B children. This can help develop more effective educational programs to improve the executive function abilities of Kindergarten B children in West Java, especially in Telaga Asih Village It is hoped that the conclusions of this research can be a guide for educators and educational planners to increase the creativity and musical intelligence of Kindergarten B children in order to optimize their executive function.